Reliability and Validity of the LPC Scale: A Reply - Rice, Robert W. (Academy of Management Review, 1979)
In this article the author responds to the comments of Schriesheim, Bannister and Money on his article and reassess the implications of certain measurement properties of the Least Preferred Co-worker (LPC) scale. The author notes that in his review he concluded that the high internal consistency of LPC has been demonstrated. He adds that, since the writing his review, five additional coefficients of internal consistency have become available. As he indicated in his initial review, the literature provides no examples of parallel form reliability as the term is usually used. As noted correctly by Schriesheim et al., alternate forms of LPC meeting the criteria of true equivalent forms have never been developed or tested.